1991
DOI: 10.1115/1.2920683
|View full text |Cite
|
Sign up to set email alerts
|

A Surface Pitting Life Model for Spur Gears: Part I—Life Prediction

Abstract: Surface pitting is a major failure mode for gears. Estimation of failure probability and service life are important in gear design. Current techniques give only a pass/fail rating based on semi-empirical methods. A predictive model for estimating service lives and failure probabilities has been developed. This paper discusses the life prediction analysis, which is based on propagation of a surface breaking crack under rolling/sliding contact conditions. The effects of both surface roughness and non-metallic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 0 publications
1
17
0
2
Order By: Relevance
“…Under these conditions, any crack propagation can be explained only after assuming an effective mode II propagation (or mode II combined with mode III). The mode II propagation was supported by Fleming and Suh [19], Keer and Bryant [20], O'regan et al [21], Kaneta [22] et al, Blake and Cheng [23], and more recently by Choi and Liu [24][25][26]. In contrast, Ding et al [8,9,27,28] clearly distinguished these two different phases.…”
Section: Subsurface Spalling and Case Crushingmentioning
confidence: 86%
“…Under these conditions, any crack propagation can be explained only after assuming an effective mode II propagation (or mode II combined with mode III). The mode II propagation was supported by Fleming and Suh [19], Keer and Bryant [20], O'regan et al [21], Kaneta [22] et al, Blake and Cheng [23], and more recently by Choi and Liu [24][25][26]. In contrast, Ding et al [8,9,27,28] clearly distinguished these two different phases.…”
Section: Subsurface Spalling and Case Crushingmentioning
confidence: 86%
“…9 will extend inward with the effect of continuing loads, and then head to the surface. Some studies [9,10] accepted the angle between the crack and the surface as 25°, but other studies [6] showed that 22°gave better results.…”
Section: Discussionmentioning
confidence: 97%
“…In the analysis reported in these figures, the effect of the values of a0 on the reliability index seems to be larger than that of aC. In practice, the initial crack size a0 could be determined using statistical approach based on enough samples; the critical crack size aC can be estimated from the critical stress intensity factor , which could be determined from experiments [38][39] or numerical simulation methods, e.g. the virtual crack extension method (VEC) [48] an important issue for reliability-based probabilistic contact fatigue analysis of gears for onshore and offshore wind turbines.…”
Section: Reliability Results and Sensitivity Studymentioning
confidence: 99%
“…The driving force for crack propagation in rolling contacts depends on the maximum shear stress [37]. In 1991, Blake and Cheng [38] developed a simplified model to calculate the mode II stress intensity factors, which is given as follows:…”
Section: Case Study Surface Pitting Modelmentioning
confidence: 99%
See 1 more Smart Citation